Violent deaths among elderly in Attica, Greece: A 5-year survey (2011–2015). (July 2019) - Nikitopoulou, Theodora; Moraitis, Konstantinos; Tsellou, Maria; Stefanidou-Loutsidou, Maria; Spiliopoulou, Chara; Papadodima, Stavroula
Abstract: According to World Health Organization (WHO) estimations, approximately 6 million people lose their lives yearly due to some kind of injury, while one-third of these incidents are due to violent acts. Violent deaths include accidents (road traffic accidents, drownings, falls, heat effects etc), suicides as well as homicides. Elderly people seem to be at greater risk due to their special characteristics as a vulnerable social group. The aim of this study was to investigate violent deaths (accidents, suicides and homicides) among elderly people in Attica, Greece, during the period 2011–2015 by examining manner of death with respect to demographic data (gender and age) and toxicological examination results. A total of 546 violent deaths among people over 65 years old were included in this study. Autopsy findings along with toxicological examination results were collected from the archives of the Department of Forensic Medicine and Toxicology of the National and Kapodistrian University of Athens. The findings of the study showed that most of the victims were male (63.74%). The overwhelming majority of violent deaths (425 cases) were accidents, 92 cases suicides, and the remaining 29 cases homicides. Drowning was the leading cause of all accidental deaths, followed by road traffic accidents. Hangings prevailed among violent suicide methods and asphyxiation presented as a predominant homicide method. Highlights: In our study the majority of violent deaths among elderly people were due to an accident. Drowning was the leading cause of all accidental deaths, followed by road traffic accidents. More than half of all suicidal deaths were due to hanging. Asphyxiation prevail among homicides.